The Effectiveness of a Training Program for the Development of Moral Intelligence among Preparatory Students (Journal Of Educational and Psychological Researches, 2022)
This current research aims to identify the effectiveness of a training program in developing moral intelligence and mutual social confidence among middle school students. The researcher made a number of hypotheses for this purpose to achieve the goal of the research.                             The researcher relied on the (Al Zawaida 2011) scale prepared according to Coles (1997), including (60) items, and the mutual social trust scale for (Nazmi 2001) based on Roter's theory including (38) items.                           The psychometric properties of each of them were verified, and a sample of female students (Al Huda Secondary) were selected, the number of its students were (60). They were randomly distributed to two groups, one of them is experimental and the other is a regulated. The equivalence process was conducted for the two research groups in terms of (time age, level of intelligence, Academic achievement for the Parents), and the training program was applied.After the completion of data collection to test the differences between the experimental group for the pre-test and the post-test,• the results of the study revealed the presence of statistically significant differences at the level (0.05) between the average performance of the members of the experimental group in the pre-test and the average performance of the members of the experimental group in the post-test on the scale (mutual social trust) scale, i.e. in favor of the post test.• The results also showed that there were no statistically significant differences at the level (0.05) between the average performance of the pre-test in the control group and the post-test for the same group (control) for the development of mutual social confidence.• The results also revealed the presence of statistically significant differences at the level (0.05) between the average performance of the members of the experimental group in the post-test. and the average performance of the members of the control group in the post-test, on, the measure of mutual social confidence, and in favor of the experimental group.• the results showed statistically significant differences between the mean scores of the pre-test for the experimental group and the mean of the deferred test scoresin favor of the back- test in mutual social confidence after the lapse of (16) days.  In the light of the results of the current research, the researcher presented a set of recommendations and proposals that expand the research ranges for subsequent research.